2001
DOI: 10.1177/036319900102600202
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Fertility Transitions: Quebec and Ontario at the Turn of the Twentieth Century

Abstract: This article uses nominal data from the Canadian Families Project national sample to analyze and compare fertility in Canada’s two largest provinces at the turn of the twentieth century. The authors argue that material and cultural factors must be considered if similarities and differences in reproductive behavior between Quebec and Ontario are to be understood. They use regression models to identify the independent influence of factors such as religion, language, occupation, class, urban versus rural residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
3
8
0
2
Order By: Relevance
“…In his study of the Swedish fertility transition, Dribe (2009) emphasized the importance of traditional supply and demand variables—education, income, mortality, urbanization and relative female wages. Although not the primary focus, several micro-level census analyses of the United States and Canada have reported significant differentials in women's fertility by spouses occupation (Haines 1978; Smith 1996; Hacker 1999; Gauvreau and Gossage 2001; Haan 2005; Gossage and Gauvreau 2007; Haines and Guest 2008). Most recently, Barnes and Guinnane (2012) have re-examined Szreter's evidence from the 1911 census of England and Wales using analysis of variance techniques and found that two-thirds of all variation in marital fertility across couples was explained by variation between social classes.…”
Section: Introductionmentioning
confidence: 99%
“…In his study of the Swedish fertility transition, Dribe (2009) emphasized the importance of traditional supply and demand variables—education, income, mortality, urbanization and relative female wages. Although not the primary focus, several micro-level census analyses of the United States and Canada have reported significant differentials in women's fertility by spouses occupation (Haines 1978; Smith 1996; Hacker 1999; Gauvreau and Gossage 2001; Haan 2005; Gossage and Gauvreau 2007; Haines and Guest 2008). Most recently, Barnes and Guinnane (2012) have re-examined Szreter's evidence from the 1911 census of England and Wales using analysis of variance techniques and found that two-thirds of all variation in marital fertility across couples was explained by variation between social classes.…”
Section: Introductionmentioning
confidence: 99%
“…Most scholars consider that the fertility decline began in England in the 1870s and fertility fell from around the same period in other Englishspeaking countries (Woods 1987;Caldwell 1999). Marital fertility started to fall from about the late 1860s in the United States, from the 1870s in English-speaking Canada and New Zealand and from the 1880s in Australia (Coghlan 1903;Jones 1971;Ruzicka and Caldwell 1977;Caldwell 1999;Gauvreau and Gossage 2001;Hacker 2003). The Australian data suggest the timing of the fertility decline varied somewhat between the colonies, falling first in Victoria from the mid-1870s and from the 1880s in all other colonies except Western Australia (Jones 1971;Quiggin 1988).…”
Section: List Of Tablesmentioning
confidence: 99%
“…In Western Europe, fertility was lower in urban areas than in rural areas at the start of the fertility decline and declined more rapidly once the decline was under way (Sharlin 1986). In Canada, also, during the fertility transition couples living in urban areas were more likely to limit their fertility than those living in rural areas (Gauvreau and Gossage 2001;Vézina et al 2014). In Utah, in the United States, on the other hand, fertility declined at the same time in rural areas and in urban areas (Bean et al 1990).…”
Section: Diffusion Theories Of the Fertility Declinementioning
confidence: 99%
See 1 more Smart Citation
“…Some differences emerge in closer studies. For example, studies concerned with the late nineteenth century show that Catholics had a higher rate of infant mortality (see Gauvreau and Gossage 2001). Catholics also tended to marry earlier than Protestants in the city of Montreal in the 1860s and their mortality rate was higher (see Olson and Thornton 2011, pp.…”
Section: Datamentioning
confidence: 99%